Time Savings when Working from Home - Cevat Giray Aksoy; Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Mathias Dolls; Pablo Zarate (Center for Economic Studies and ifo Institute (CESifo), 2023)
We quantify the commute time savings associated with work from home, drawing on data for 27 countries. The average daily time savings when working from home is 72 minutes in our sample. We estimate that work from home saved about two hours per week per worker in 2021 and 2022, and that it will save about one hour per week per worker after the pandemic ends. Workers allocate 40 percent of their time savings to their jobs and about 11 percent to caregiving activities. People living with children allocate more of their time savings to caregiving.
Keywords: D10; J22; L23; R41; 330; work from home; commute times; allocation of time savings